Structural Aspects of Diaquotetrakis(imidazole)cobalt(II) Chloride - Meera, P.; Amutha Selvi, M.; Dayalan, A. (Asian Journal of Chemistry, 2012)
A pink coloured cobalt(II) complex viz., [Co(Imi)4(H2O)2]Cl2 was prepared by mixing cobalt(II) chloride with imidazole in 1:4 molar ratio in acetone. The complex was characterized by UV, IR, TG-DTA and single crystal XRD studies. The EPR spectrum of the complex proved its paramagnetic nature which was further analyzed by magnetic susceptibility studies. Susceptibility measurements showed the presence of three unpaired electrons accounting for the high spin nature of the complex.